Emoji captcha; a novel option for protect web pages (Nexo Revista Científica, 2021)
In this work, a development of a captcha variant is presented with the use of a gif image, composed of 6 frames; each frame is made up of 9 images arranged in a 3 by 3 matrix; Each image used expresses an emotion from a set of 5 basic emotions. Each of the 9 sectors into which the gif is divided is assigned a digit mark, in order for the user to recognize an emotion within the gif and using their cognitive skills to relate this emotion to a number and, in this way, identify the right answer. A simple and safe alternative is proposed for the protection of websites, ideal for a wide range of users, regardless of their age or computer knowledge, this is due to the use of emotions that are recognized by every human being. Current developments perform network traffic analysis and response time to identify if the user is human or a malicious program, allowing attackers to access other types of user information in a simpler way, the advantage of this proposal comes from fact of the regeneration of the captcha and the redistribution of the identification numbers every 2 minutes, reinforced by a series of applied distortions, in this way the attackers cannot access extra information from the user and due to the regeneration time makes it unfeasible for him.